Delineation of the genetic causes of complex epilepsies in South African pediatric patients - Esterhuizen, Alina (Division of Human Genetics, 2023)
Background Sub-Saharan Africa bears the highest burden of epilepsy worldwide. A proportion is presumed to be genetic, but this aetiology is buried under the burden of infections and perinatal insults, in a setting of limited awareness and few options for testing. Children with developmental and epileptic encephalopathies (DEEs), are most severely affected by this diagnostic gap, as the rate of actionable findings is highest in DEE-associated genes. This research study investigated the genetic architecture of epilepsy in South African (SA) children clinically diagnosed with DEE, highlighting the clinical utility of informative genetic findings and relevance to precision medicine for DEEs in a resource-constrained setting. Methods A group of 234 genetically naïve SA children with drug-resistant epilepsy and a diagnosis or suspicion of DEE, were recruited between 2016 and 2019. All probands were genetically tested using a DEE gene panel of 71 genes. Of the panel-negative probands, 78 were tested with chromosomal microarray and 20 proband/parent trios underwent exome sequencing. Statistical comparison of electroclinical features in children with and without candidate variants was performed to identify characteristics most likely predictive of a positive genetic finding. Results Pathogenic/likely pathogenic (P/LP) variants were identified in 41/234(17.5%) * probands. Of these, 29/234(12.4%) * were sequence variants in epilepsy-associated genes and 12/234(5.1%) * were genomic copy number variants (CNVs). Sixteen variants of uncertain significance (VUS) were detected in 12 patients. Of the 41 children with P/LP variants, 26/234(11%) had variants supporting precision therapy. Multivariate regression modelling highlighted neonatal or infantile-onset seizures with movement abnormalities and attention difficulties as predictive of a positive genetic finding. This, coupled with an emphasis on precision medicine outcomes, was used to propose the pragmatic “Think-Genetics” decision tree for early recognition of a possible genetic aetiology, pragmatic testing, and multidisciplinary consultation. Conclusion The findings presented here emphasise the relevance of an early genetic diagnosis in DEEs and highlight the importance of access to genetic testing. The “Think-Genetics” strategy was designed for early recognition, appropriate interim management, and genetic testing for DEEs in resource constrained settings. The outcomes of this study emphasise the pressing need for augmentation of the local genetic laboratory services, to incorporate gene panels and exome sequencing. *These percentages were rounded off to whole numbers in the published articles included in this thesis (i.e., rounded off to 18%, 12% and 5%, respectively).